Analysis of Drug Distribution from Pharmaceutical Warehouse to Pharmaceutical Installation of Siti Fatimah Hospital Palembang in 2025 - Poppy Angraeni Wulandari; Amelia Soyata; Sabda Wahab (JURNAL LENTERA ILMIAH KESEHATAN, 2026)
This study aims to analyze the mechanisms, flow, and challenges of drug distribution from the pharmacy warehouse to the pharmacy installation at RSUD Siti Fatimah Palembang. This research used a descriptive observational method with a quantitative approach. Data were collected through direct observation, structured interviews, and document review using a checklist instrument based on the Indonesian Ministry of Health Regulation Number 72 of 2016 regarding Pharmacy Service Standards in Hospitals.The results showed that the mechanism and flow of drug distribution were implemented in accordance with pharmacy service standards, achieving a compliance rate of 100%. However, several operational challenges were identified, including discrepancies in the quantity and type of drugs compared to requests, as well as delays in distribution that resulted in stock shortages at service units.This study concludes that the drug distribution system at RSUD Siti Fatimah Palembang has complied with existing standards, but optimization of the pharmacy logistics information system and improved coordination between units are needed to reduce distribution constraints.